Country Launch (Bangladesh): CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience - International Rice Research Institute (International Rice Research Institute, 2022)
The report documents the results of the country launch of the CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD) held in Dhaka City, Bangladesh on 10 August 2022.